"Woman In The Mortuary" Psychological Review (Journal of Namibian Studies : History Politics Culture, 2023)
Musharraf Alam Zauqi is a famous novelist and fiction writer of Urdu literature. In "Woman in the Mortuary", the psychology of human life, social behavior, economic depression, conflicting behavior with minorities, violation of rights are presented. Musharraf Alam Zauqi gave a wide canvas to this psychological oppression and exploitation in the novel "Murda". Wrote "Woman in Box". The novel "Woman in the Mortuary" deals with psychological confusion and many issues such as gender, politics, murder, death and life struggle, which helps in presenting the novel in a multi-faceted perspective.